THE ROLE OF NADRAN TRADITION AS A MARITIME EDUCATION BASED ON THE LOCAL WISDOM - Lingga Utami; Dadan Saeful Ramadhan; Rengga Akbar Munggaran (Jurnal PPI Dunia, 2018)
In order to build Indonesia into the global maritime axis created five pillars of the global maritime axis,first is rebuilding the maritime culture of Indonesia as a form of empowerment through maritime potential aspects of education local wisdom-based. Maritime education based on the local wisdom is believed to be a form of strengthening cultural values as the basic identity of coastal communities in Cirebon is Nadran tradition. Nadran tradition carried on by the fishing communities have social values, culture and religion play a role in order to give thanks for the Earth results obtained. This study used a qualitative approach with descriptive method of analysis through data collection techniques of observation, in-depth interview and documentation study. Location of the study take one area in Cirebon is Samadikun. Informants consisted of Fishermen, Kebayan (readers of prayer), Pemangku Hajat (indigenous stakeholders), and a part of Keraton Cirebon. The results showed that the tradition of maritime education is a based on the local knowledge to introduce an element of social values, culture and religion of Nadran tradition. Process of Nadran tradition involves not only the fishermen as the main object in the show but the role of a part of Keraton Cirebon as indigenous stakeholders and preservation of culture. Nadran tradition has meaning social values, culture and religion are very thick to be used as a guide in conducting social relations in society. The conclusion that Nadran tradition as a representation of maritime education based on the local wisdom that contains the values of social, cultural and religious that are still run by Samadikun communities and every value internalized to the next generations. It is intended that the meaning of each process of Nadran tradition can be maintained continuously and sustainably.